ANALISIS KECERDASAN INTERPERSONAL ANAK USIA DINI DALAM KEGIATAN ANGKLUNG DI TK ABA 01 MEDAN - Naya Efendi, Sri; Sari Lubis, May (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze early childhood interpersonal intelligence in angklung activities at TK ABA 01 Medan, viewed from three dimensions: social sensitivity, social insight, and social communication. The method used was a descriptive qualitative approach. The subjects consisted of seven Group B children participating in angklung activities, with the classroom teacher and angklung instructor serving as supporting informants. The object of the study was children’s interpersonal intelligence as observed during the activities. Data were collected through observation, interviews, documentation, and reflective notes. The results show that angklung activities provide an effective learning context for stimulating children’s interpersonal intelligence. In the dimension of social sensitivity, children demonstrated empathy and prosocial behavior through care, cooperation, and willingness to help peers, in line with Anderson’s theory. In the dimension of social insight, children were able to understand roles, rules, and turn-taking, and solve simple problems with varying levels of independence, reflecting the ability to interpret social norms. In the dimension of social communication, children communicated effectively with teachers and peers and responded well to the instructor’s instructions. However, the development of interpersonal intelligence was not evenly distributed due to individual differences. Overall, angklung activities provide opportunities for children to develop cooperation, communication, social understanding, and positive interpersonal relationships.